DOI: 10.26756/th.2020.166
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions of the effect of leadership on school climate

Abstract: This mixed methods research examines the relationship between principal leadership and school climate. A sample of 63 elementary teachers evaluated their school climate and leadership through the OCDQ-RE and the MLQ-5X and expressed their views on both by responding to open-ended questions. Quantitative analysis for both questionnaires, correlations between the dimensions of the two instruments and qualitative analysis of the open-ended questions were conducted to determine the leadership characteristics and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…Actually, research on non-teaching staff is not only scarce in Lebanon but also internationally. This scarcity in international and (Ibrahim, 2019). There are, however, research studies in Lebanon that have addressed constructs such as trust (Ghamrawi, 2011), engagement (Nabhani et al, 2012), burnout (El Helou et al, 2016, and equity (Maaliki, 2018).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, research on non-teaching staff is not only scarce in Lebanon but also internationally. This scarcity in international and (Ibrahim, 2019). There are, however, research studies in Lebanon that have addressed constructs such as trust (Ghamrawi, 2011), engagement (Nabhani et al, 2012), burnout (El Helou et al, 2016, and equity (Maaliki, 2018).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…There are, however, research studies in Lebanon that have addressed constructs such as trust (Ghamrawi, 2011), engagement (Nabhani et al, 2012), burnout (El Helou et al, 2016, and equity (Maaliki, 2018). Research can be found that focuses on school leadership and its effect on constructs related to school climate, such as motivation, commitment, and decision-making (Addam, 2006;Berjaoui, 2013;Gharib, 2011;Ibrahim, 2019;Saheb, 2012).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Following the legal ban on corporal punishment, LaRoche (2014) and Ibrahim (2019) report that learner disciplinary issues in schools are on the rise and pose a significant challenge for many teachers. Studies show that learners conduct issues in schools have an impact on teachers' morale and can be very problematic.…”
Section: Rationale For the Studymentioning
confidence: 99%